Development of Interactive Video and Wordwall Evaluation Media on Pancasila in Elementary School - Akbar, Ibhan; Fadhila, Laila; Amini, Raisyah (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2025)
In the world of education, teachers as educators are expected to be able to utilize technology in classroom learning activities. The study aims to develop interactive learning videos and wordwall evaluation media on Pancasila SD material. This study uses R&D steps with ADDIE stages (analyze, design, development, implementation, evaluation). Data collection instruments use questionnaires and interviews. Validation through questionnaires assesses aspects of material, media and language. The results of the questionnaire distribution validation assessment by assessing aspects of material, media and language obtained an average value of the material aspect of 93⁒ with a very good category, the media aspect assessment of 91⁒ with a very good category, and the language aspect questionnaire validation assessment of 92⁒ very good category. The results of student interviews felt very helped by the learning video media and the fun wordwall evaluation media and aroused students' enthusiasm for learning. The results of the interactive learning video and wordwall evaluation media trials have met the valid, practical and feasible categories for teachers and students to implement in the learning process in the classroom.